1994
DOI: 10.1136/adc.71.6.497
|View full text |Cite
|
Sign up to set email alerts
|

Potentially dangerous sleeping environments and accidental asphyxia in infancy and early childhood.

Abstract: Infants and young children may be exposed to a variety of dangerous situations when left sleeping in cots, chairs, or beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 6 publications
3
60
0
Order By: Relevance
“…A recent review found the mean age of such infants to be 10 months, with an upper limit being 3 years [22].…”
Section: Asphyxial Deaths Cot/bed Asphyxiasmentioning
confidence: 98%
“…A recent review found the mean age of such infants to be 10 months, with an upper limit being 3 years [22].…”
Section: Asphyxial Deaths Cot/bed Asphyxiasmentioning
confidence: 98%
“…Sleep environments are also implicated in infant suffocation deaths, and various lethal sleep environments have been described in detail (Byard et al 1994;. Regardless of the sleep locations, lack of 7 supervision was a factor in each of the cases examined.…”
Section: Other Sleep-related Infant Deathsmentioning
confidence: 99%
“…Wedging involving a bed is not a new pattern of suffocation, 10,11 nor is it a pattern that occurs only in the United States. Wedging suffocation deaths attributed to slipping between a mattress and bed sides or wall have been reported in South Australia 12 and in England and Wales. 9 In the latter study, beds and cots were implicated in nearly one third of accidental asphyxia deaths among children.…”
Section: Wedgingmentioning
confidence: 99%